A narrative-informed evaluation of tree of life for parents of children with physical health conditions. (January 2021) - Haselhurst, Jessica; Moss, Kate; Rust, Stewart; Oliver, James; Hughes, Rhian; McGrath, Catherine; Reed, Daniel; Ferguson, Lucy; Murray, Joanne
Background: Parents of children with chronic health conditions can face many challenges. The Tree of Life narrative therapy group intervention aims to connect parents with their skills and resources before collectively exploring the 'storms' (challenges) they face. A narrative-informed evaluation aimed to story the parents' experiences of attending the group. Methods: Seven parents attended a Tree of Life group intervention and then participated in a narrative-informed group interview to generate stories regarding their experience of the group. The interview was recorded with consent and later transcribed. Results: A thematic analysis was undertaken and highlighted that the group offered parents a 'safe place to stand' to talk about difficulties; a different perspective on their situation; connection with the skills of other parents; new ideas to introduce more independence to their child; and togetherness within the 'storms' (challenges). Conclusions: The narrative-informed evaluation offered opportunities to further thicken parents' preferred identity stories whilst also contributing to the evidence base of narrative-informed group interventions for parents.